Preparation method of silicon-calcium slag-ardealite-based shrinkage reducing agent for ultra-high performance concrete
Through the preparation method of silicon calcium residue-phosphogypsum-based shrinkage agent, wet grinding process and acid-base neutralization reaction, combined with the control of concave and convex rod soil, the problems of UHPC shrinkage and mechanical properties were solved, and the effect of reducing shrinkage and improving early strength was achieved.
Patent Information
- Application Number
- CN202411652689.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing ultra-high performance concrete (UHPC) reduction measures have problems such as reduced shrinkage but decreased overall mechanical properties, insufficient expansion agent response, or cracking, and delayed hydration of the shrinkage agent is not conducive to early strength development.
The preparation method of silicon calcium residue-phosphogypsum-based shrinkage agent is adopted, and the acid-base neutralization reaction and impurity pretreatment are carried out through the wet grinding process to promote the hydration reaction of silicon calcium residue and the solidification of phosphogypsum, and the ion release rate is controlled in combination with the concave and convex rod soil to reduce the shrinkage of UHPC.
It effectively reduces the shrinkage of UHPC and improves its early mechanical properties, while having no adverse effects on fluidity and settling time, achieving efficient utilization of resources.
Smart Images

Figure BDA0005141365730000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing a calcium silicate slag-phosphogypsum based shrinkage reducing agent. Background Art
[0002] Ultra-high performance concrete (UHPC) is usually designed and prepared using the closest packing theory. Its high density makes it a fiber-reinforced cement-based composite material with ultra-high mechanical properties, durability and toughness. It is widely used in the preparation of large-span pedestrian bridges, highway and railway bridges, thin-walled silos, nuclear waste tanks, steel cable anchor reinforcement plates, ATM protective shells, etc.
[0003] The amount of adhesive used in ultra-high performance concrete is much higher than that in ordinary concrete, and in order to reduce the interface transition zone and improve toughness, it is usually necessary to remove coarse aggregate, which makes UHPC shrink larger and has a higher risk of cracking. At present, there are three commonly used technical methods for UHPC shrinkage reduction measures: adding expansion agents to produce volume expansion to compensate for shrinkage; adding internal curing agents to increase the relative humidity inside the concrete to reduce shrinkage; using shrinkage reducers to reduce the surface tension of capillaries to reduce shrinkage.
[0004] The above methods or a combination of several methods can reduce the shrinkage of UHPC to a certain extent, but the internal curing agent is usually a porous material, which increases the porosity of UHPC and easily causes a decrease in the overall mechanical properties of UHPC; the expansion reaction of the expansive agent usually requires sufficient water, but the water-binder ratio of UHPC is relatively low (0.12-0.18), and the expansive agent is difficult to fully react, resulting in insufficient expansion. At the same time, the unreacted expansive agent in UHPC is prone to violent reaction when it encounters water later, causing the UHPC structure to crack or even pulverize; the shrinkage reducer will delay the hydration of cement and prolong the cement setting time, which is not conducive to the development of the early strength of UHPC.
[0005] Therefore, developing a shrinkage reducer that can effectively reduce the shrinkage of UHPC while having no adverse effect on the strength of UHPC has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] The present invention aims to provide a method for preparing a calcium silicate slag-phosphogypsum based shrinkage reducer for ultra-high performance concrete, which can effectively reduce the shrinkage of UHPC without adversely affecting the fluidity and setting time, and is beneficial to improving the early mechanical properties of UHPC.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0008] A method for preparing a calcium silicate slag-phosphogypsum-based shrinkage reducing agent for ultra-high performance concrete comprises the following steps:
[0009] 1) mixing and wet-grinding the original calcium silicate slag, the original phosphogypsum and the dispersion stabilizer, aging, washing, filtering and drying to obtain a mixture A;
[0010] 2) subjecting mixed material A to pressure steam curing, and then drying and crushing at low temperature to obtain mixed material B;
[0011] 3) Add attapulgite to mixture B and mix evenly to obtain a calcium silicate slag-phosphogypsum based shrinkage reducing agent for ultra-high performance concrete.
[0012] The present invention grinds the original calcium silicate slag and the original phosphogypsum to a certain fineness through a wet grinding process, utilizes an acid-base neutralization reaction to fully react alkaline substances such as sodium hydroxide in the calcium silicate slag and acidic substances such as phosphoric acid in the phosphogypsum to generate sodium salt, thereby adjusting the pH value of the mixture, and then removes the sodium salt generated by the acid-base reaction through aging, washing, filtering and other means, and pre-treats the soluble phosphorus, soluble fluorine, organic substances and the like in the phosphogypsum, and then, through pressure steam curing, the β-C2S in the calcium silicate slag undergoes a prehydration reaction to generate calcium hydroxide and CSH gel, and the generated Calcium hydroxide reacts with the residual soluble fluorine in the phosphogypsum to generate calcium fluoride, and reacts with eutectic phosphorus and the residual soluble phosphorus to generate calcium phosphate, so as to solidify the soluble fluorine, soluble phosphorus and eutectic phosphorus, and effectively reduce the adverse effects of impurities in calcium silicate slag and phosphogypsum on the working performance, hydration process, mechanical properties and the like of cement concrete. At the same time, the CSH gel generated by the prehydration reaction of calcium silicate slag can be used as a hydration nucleation inducer for cement concrete to improve its early strength, and the generated insoluble calcium fluoride and calcium phosphate can be used as nucleation dispersion reinforcement phases to improve its overall mechanical properties. In addition, in order to effectively control the rate at which dihydrate gypsum in the phosphogypsum reacts with cement to generate calcium sulfonate with expansion effect, and to avoid the calcium sulfonate reaction rate being too fast, forming a large number of internal defects in the cement concrete, and causing the mechanical properties of the component to decrease, the present invention adsorbs the shrinkage reducer of the present invention by adding attapulgite with a layered chain structure, and reduces the release rate of its effective components in the cement hydration reaction.
[0013] Optionally, in step 1, the pH value of the original calcium silicate slag is 11-13, and the water content is 15-30wt%; the pH value of the original phosphogypsum is 1.5-4.5, and the water content is 10-20wt%.
[0014] Optionally, the original calcium silicate slag and original phosphogypsum in step 1 are mixed in a mass ratio of (1.8-2.5):1, the water-to-material ratio of the wet grinding process is 2-3, and the ball-to-material ratio is 6-8.
[0015] Optionally, step 1 further includes respectively measuring the moisture content of the original calcium-silicon slag and the original phosphogypsum, and determining the amount of water added for wet grinding based on the moisture content of the original calcium-silicon slag and the original phosphogypsum.
[0016] The present invention controls the amount of water used for wet grinding by using the water content and the water-to-material ratio, thereby avoiding the influence of the water content of the original calcium-silicon slag and the original phosphogypsum on the dispersion effect of the materials during the wet grinding process, thereby facilitating the improvement of the grinding efficiency of the original calcium-silicon slag and the original phosphogypsum, and the separation effect of the impurities in the original calcium-silicon slag and the original phosphogypsum. In addition, the original calcium-silicon slag and the original phosphogypsum are mixed at a mass ratio of (1.8-2.5):1 in the present invention, which can ensure that the acid-base neutralization reaction of the original calcium-silicon slag and the original phosphogypsum is fully carried out. In addition, the pH value of the mixture A can be made within the range of 9-11 by controlling the number of washing and filtering times, which is conducive to the high reaction degree of the calcium-silicon slag hydration reaction during the subsequent autoclave curing process, and can promote the solidification of soluble fluorine, soluble phosphorus, and eutectic phosphorus in the phosphogypsum.
[0017] Optionally, the dispersion stabilizer is composed of polyethylene glycol and wollastonite fiber; the amount of polyethylene glycol is 0.05-0.08% of the total mass of the original calcium silicate slag and the original phosphogypsum; the amount of wollastonite fiber is 1-2% of the total mass of the original calcium silicate slag and the original phosphogypsum.
[0018] Optionally, the wollastonite fiber has an aspect ratio of 15-20, a length of 400-500 μm, and a width of 20-30 μm.
[0019] Optionally, the polyethylene glycol is one of PEG400 and PEG600.
[0020] The present invention uses polyethylene glycol and wollastonite fiber as a dispersing stabilizer in the wet grinding process, wherein polyethylene glycol can reduce the surface tension of the liquid and promote better dispersion of solid particles in the liquid, and the micro-nano needle-like structure of wollastonite fiber can be interspersed between solid particles in the wet grinding process to prevent solid particles from agglomerating, and on the other hand, the micro-nano size enables it to have a certain adsorption effect on solid particles, avoiding slurry stratification during wet grinding, affecting the grinding efficiency of calcium silicate slag and phosphogypsum. At the same time, after the wet grinding is completed, the slurry is washed, filtered, and dried, and the wollastonite fiber forms a mixture A together with the calcium silicate slag and the calcium silicate slag, which can become a nucleating agent for the hydration reaction of the calcium silicate slag in the subsequent pressure steam curing process, and promote the reverse of its hydration reaction.
[0021] Optionally, in step 1), the grinding speed of the wet grinding process is 100-200 rpm, and the grinding time is 35-45 min.
[0022] Optionally, the specific surface area of the mixture A obtained in step 1) is not less than 300m 2 / kg; moisture content is 20-25wt%.
[0023] Optionally, the steam pressure of the pressure steam curing in step 2) is 1.1-1.3 MPa, and the steam temperature is 185-200°C.
[0024] The present invention can provide suitable humidity for the reaction of calcium-silicate slag and phosphogypsum by controlling the fineness and moisture content of the mixture A and the curing conditions of the autoclave curing, and ensure an effective contact area between the particles, thereby promoting a higher reaction rate and reaction degree between the calcium-silicate slag and the phosphogypsum.
[0025] Optionally, the drying temperature of the low-temperature drying in step 2) is 40-45°C.
[0026] Optionally, in step 3), the mass ratio of the mixture B to the attapulgite is 1:(0.05-0.1); the fineness of the attapulgite is 200 mesh-325 mesh.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention is based on the acid-base neutralization reaction and uses a wet grinding process to pretreat impurities and adjust the pH of the original calcium silicate slag and original phosphogypsum, and then solidifies the soluble fluorine, soluble phosphorus and eutectic phosphorus in the phosphogypsum through the hydration reaction of the calcium silicate slag. Finally, the ion release rate is controlled by the layered chain structure of attapulgite to obtain a calcium silicate slag-phosphogypsum-based shrinkage reducing agent with good shrinkage reduction effect. When the calcium silicate slag-phosphogypsum-based shrinkage reducing agent prepared by the present invention is used for UHPC, the shrinkage of UHPC can be greatly reduced, and at the same time, it has no adverse effect on the fluidity and setting time of UHPC, and is beneficial to improving the early mechanical properties of UHPC.
[0029] 2. The preparation process of the present invention is simple, and the effective utilization of calcium-silicate slag and phosphogypsum is achieved, providing a new direction for the resource utilization of calcium-silicate slag and phosphogypsum. DETAILED DESCRIPTION
[0030] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0031] The specific implementation provides
[0032] Example 1
[0033] A method for preparing a calcium silicate slag-phosphogypsum-based shrinkage reducing agent for ultra-high performance concrete, specifically comprising the following steps:
[0034] 1) The water content of the original calcium-silicon slag and the original phosphogypsum was measured respectively. The pH value of the original calcium-silicon slag was 11.53, the water content was 25.4%, and the pH value of the original phosphogypsum was 2.55, the water content was 15.8%;
[0035] 2) weighing original calcium silicate slag and original phosphogypsum in a mass ratio of 1.8:1;
[0036] 3) The amount of water added for wet grinding is determined according to the mass, moisture content, and water-to-material ratio of the original calcium-silicon slag and original phosphogypsum in wet grinding process, wherein the amount of water added for wet grinding W satisfies the following conditions: W=Wr×(m1+m2)-m1×W1 / (1+W1)-m2×W2 / (1+W2). In this embodiment, the water-to-material ratio is set to 2;
[0037] 4) The weighed original calcium silicate slag, original phosphogypsum and water were put into a wet mill with a ball-to-material ratio of 6, and a dispersing stabilizer composed of polyethylene glycol and wollastonite fiber was added. The mill was ground at a grinding speed of 100 rpm for 45 minutes, then aged for 6 hours, washed and filtered until the pH value of the supernatant was within the range of 9-11, and then dried at 105°C to obtain a granular material with a moisture content of 20% and a specific surface area of 320 m 2 / kg of mixed material A, wherein the grinding media is composed of steel balls with diameters of 5mm, 10mm, and 20mm, and the mass ratio of the steel balls with different diameters is 5mm:10mm:20mm=1:2:1; the amount of polyethylene glycol (PEG600) in the dispersion stabilizer is 0.05% of the total mass of the original calcium silicate slag and the original phosphogypsum; the amount of wollastonite fiber in the dispersion stabilizer is 1% of the total mass of the original calcium silicate slag and the original phosphogypsum, and the length of the wollastonite fiber is 450μm, the width is 25μm, and the aspect ratio is 18;
[0038] 5) Mixture A is placed under the conditions of a steam pressure of 1.1 MPa and a steam temperature of 185° C. for pressure steam curing for 8 hours. After the pressure steam curing is completed, it is low-temperature dried at 45° C. and then ground in a ball mill for 2 minutes to obtain mixture B;
[0039] 6) Add a certain amount of attapulgite with a fineness of 325 mesh to mixture B, mix evenly, and obtain a calcium silicate slag-phosphogypsum based shrinkage reducing agent for ultra-high performance concrete, wherein the mass ratio of mixture B to attapulgite is 1:0.05.
[0040] Example 2
[0041] A method for preparing a calcium silicate slag-phosphogypsum-based shrinkage reducing agent for ultra-high performance concrete, specifically comprising the following steps:
[0042] 1) The water content of the original calcium-silicon slag and the original phosphogypsum was measured respectively. The pH value of the original calcium-silicon slag was 11.53, the water content was 25.4%, and the pH value of the original phosphogypsum was 2.55, the water content was 15.8%;
[0043] 2) weighing original calcium silicate slag and original phosphogypsum in a mass ratio of 2.5:1;
[0044] 3) Determine the amount of water added for wet grinding according to the mass, moisture content, and water-to-material ratio of the original calcium-silicon slag and original phosphogypsum in wet grinding process, wherein the amount of water added for wet grinding W satisfies the following conditions: W=Wr×(m1+m2)-m1×W1 / (1+W1)-m2×W2 / (1+W2) and in this embodiment, the water-to-material ratio is set to 3;
[0045] 4) The weighed original calcium silicate slag, original phosphogypsum and water were put into a wet mill with a ball-to-material ratio of 8, and a dispersion stabilizer composed of polyethylene glycol and wollastonite fiber was added, and the mill was ground at a grinding speed of 200 rpm for 35 minutes, then aged for 6 hours, washed and filtered until the pH value of the supernatant was within the range of 9-11, and dried at 105°C to obtain a moisture content of 20% and a specific surface area of 350 m 2 / kg of mixed material A, wherein the grinding media consists of steel balls with diameters of 5 mm, 10 mm, and 20 mm, the mass ratio of the steel balls with different diameters is 5 mm:10 mm:20 mm=1:2:1, the dispersion stabilizer consists of polyethylene glycol (PEG400) and wollastonite fiber, the amount of polyethylene glycol is 0.08% of the total mass of the original calcium silicate slag and the original phosphogypsum; the amount of wollastonite fiber is 2% of the total mass of the original calcium silicate slag and the original phosphogypsum, and the length of the wollastonite fiber is 450 μm, the width is 25 μm, and the aspect ratio is 18;
[0046] 5) Place mixed material A under the condition of steam pressure of 1.3 MPa and steam temperature of 200° C. for pressure steam curing for 6 hours. After the pressure steam curing is completed, dry it at 45° C. and then grind it in a ball mill for 2 minutes to obtain mixed material B;
[0047] 6) Add a certain amount of attapulgite with a fineness of 200 mesh to mixture B, mix evenly, and obtain a calcium silicate slag-phosphogypsum based shrinkage reducing agent for ultra-high performance concrete, wherein the mass ratio of mixture B to attapulgite is 1:0.1.
[0048] Comparative Example 1
[0049] Example 1 was repeated, and the amount of dispersion stabilizer added during the wet grinding process was 0. The specific surface area of the mixture A obtained in this comparative example was 260 m 2 / kg.
[0050] Comparative Example 2
[0051] Example 1 was repeated, and polyethylene glycol was used as the dispersing stabilizer in the wet grinding process, and the amount used was 0.05% of the total mass of the original calcium silicate slag and the original phosphogypsum. The specific surface area of the mixture A obtained in this comparative example was 300m2 / kg.
[0052] Comparative Example 3
[0053] Example 1 was repeated, and wollastonite fiber was used as the dispersing stabilizer in the wet grinding process, and the amount used was 1% of the total mass of the original calcium silicate slag and the original phosphogypsum. The specific surface area of the mixture A obtained in this comparative example was 280 m 2 / kg.
[0054] Comparative Example 4
[0055] Example 1 was repeated, except that the amount of attapulgite added was 0.
[0056] The suitable amount of the calcium silicate slag-phosphogypsum-based shrinkage-reducing agent for ultra-high performance concrete obtained by the present invention in ultra-high performance concrete is 10-20% (internal addition) of the total amount of cementitious materials. The calcium silicate slag-phosphogypsum-based shrinkage-reducing agent for ultra-high performance concrete obtained by Examples 1-2 of the present invention and Comparative Examples 1-4 is used in ultra-high performance concrete, and the samples are cured to a specified age, and their performance is tested, wherein the amount thereof is 15% (internal addition) of the total amount of cementitious materials, and the blank sample is an ultra-high performance concrete sample without the shrinkage-reducing agent of the present invention. The blank sample and the ultra-high performance concrete mix ratio (kg / m 3 ) are shown in Table 1, and the test results are shown in Table 2.
[0057] Table 1
[0058] cement Silica Fume Microbeads Shrinkage Reducing Agent water Polycarboxylate water reducer Quartz sand Steel Fiber 726 145 166 0 176 8.3 1037 156 618 123 141 155 176 8.3 1037 156
[0059] Table 2
[0060]
[0061] As can be seen from Table 2, in the preparation process of ultra-high performance concrete, adding the calcium silicate slag-phosphogypsum-based shrinkage reducer of the present invention can greatly reduce the shrinkage of the specimen, and at the same time improve the early strength of the specimen. Although the later strength is reduced, the reduction is not significant, and the shrinkage reducer of the present invention has no obvious adverse effect on the working performance of the slurry. Relative to Example 1, during the wet grinding process, the dispersion stabilizer is removed (Comparative Example 1), or only polyethylene glycol and wollastonite fiber are used as dispersion stabilizers (Comparative Examples 2 and 3), the grinding efficiency of the mixture is reduced, resulting in a decrease in the specific surface area of the mixture and a decrease in the reaction activity, which in turn leads to a decrease in the early strength of the prepared UHPC, and the later strength is also reduced due to the decrease in reaction activity, and at the same time leads to an increase in the 28d shrinkage. Relative to Example 1, the attapulgite is removed (Comparative Example 4), and the 1d strength of the specimen is greatly improved, but due to the SO4 in the phosphogypsum 2-The release rate is too fast, resulting in a higher rate of reaction with cement hydration products to form calcium sulfonate, which increases the number of internal defects in the paste and increases the strength reduction of the specimen after 3 days.
[0062] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a calcium silicate slag-phosphogypsum-based shrinkage reducing agent for ultra-high performance concrete, characterized in that The following steps are involved: 1) mixing and wet-grinding the original calcium silicate slag, the original phosphogypsum and the dispersion stabilizer, aging, washing, filtering and drying to obtain a mixture A; 2) subjecting mixed material A to pressure steam curing, and then drying and crushing at low temperature to obtain mixed material B; 3) Add attapulgite to mixture B and mix evenly to obtain a calcium silicate slag-phosphogypsum based shrinkage reducing agent for ultra-high performance concrete.
2. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that In step 1, the pH value of the original calcium silicate slag is 11-13, and the water content is 15-30wt%; the pH value of the original phosphogypsum is 1.5-4.5, and the water content is 10-20wt%.
3. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that In step 1, the original calcium silicate slag and the original phosphogypsum are mixed in a mass ratio of (1.8-2.5):1, the water-to-material ratio of the wet grinding process is 2-3, and the ball-to-material ratio is 6-8.
4. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that Step 1 also includes measuring the moisture content of the original calcium-silicon slag and the original phosphogypsum respectively, and determining the amount of water added for wet grinding based on the moisture content of the original calcium-silicon slag and the original phosphogypsum.
5. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that The dispersion stabilizer is composed of polyethylene glycol and wollastonite fiber; the amount of the polyethylene glycol is 0.05-0.08% of the total mass of the original calcium silicate slag and the original phosphogypsum; the amount of the wollastonite fiber is 1-2% of the total mass of the original calcium silicate slag and the original phosphogypsum.
6. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that The aspect ratio of the wollastonite fiber is 15-20, the length is 400-500 μm, and the width is 20-30 μm; the polyethylene glycol is one of PEG400 and PEG600.
7. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that Step 1) The grinding speed of the wet grinding process is 100-200 rpm, and the grinding time is 35-45 min.
8. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that Step 1) The specific surface area of the obtained mixture A is not less than 300m 2 / kg; moisture content is 20-25wt%.
9. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that The steam pressure of the pressure steam curing in step 2) is 1.1-1.3 MPa, and the steam temperature is 185-200°C; the drying temperature of the low-temperature drying is 40-45°C.
10. The method for preparing the calcium silicate slag-phosphogypsum based shrinkage reducing agent according to claim 1, characterized in that In step 3), the mass ratio of the mixture B to the attapulgite is 1:(0.05-0.1); the fineness of the attapulgite is 200 mesh-325 mesh.
Citation Information
Patent Citations
Anti-seepage and anti-cracking waterproof agent for constructional engineering
CN111847979A
Low shrinkage ultrahigh strength fiber-reinforced cement composition, low shrinkage ultrahigh strength fiber-reinforced mortar or concrete, and low shrinkage ultrahigh strength cement admixture
JP2009084095A